Electric Vehicles in the Digital Discourse: A Sentiment Analysis of Social Media Engagement for Turkey - Hafize Nurgul Durmus Senyapar (SAGE Open)
The adoption of electric vehicles (EVs) is a critical component of transitioning toward sustainable transportation systems. Understanding public sentiment and engagement regarding EVs is essential for policymakers, industry participants, and scholars to address challenges and opportunities in the EV market effectively. This study conducted a comprehensive analysis of public sentiment and engagement concerning EVs on social media platforms. One thousand posts from Facebook, Instagram, and X were analyzed to provide a cohesive narrative encompassing public opinion toward EVs and offering a roadmap for this disruptive technology’s future. The results indicate a significant level of user engagement, supported by 7,000 collective interactions and an impressive 4,300 shares. Predominantly positive sentiments, comprising 83.2% of the analyzed posts, highlight the widespread optimism regarding EV technology. The discourse encompasses various subjects, including brand preferences, financial implications, infrastructure, and environmental aspects. The insights gleaned from these results are of immense value to policymakers, industry participants, and scholars as they navigate the ever-changing terrain of electric mobility.